Diagnostic accuracy of point‐of‐care ultrasound compared to standard‐of‐care methods for endotracheal tube placement in neonates. Issue 7 (17th May 2022) - Ariff, Shabina; Ali, Khushboo Q.; Tessaro, Mark O.; Ansari, Uzair; Morris, Shaun; Soofi, Sajid Bashir; Merali, Hasan S.
Abstract: Introduction: Point‐of‐care ultrasound (POCUS) is a valuable tool to determine endotracheal tube (ETT) placement; however, few studies have compared it with standard confirmation methods. We evaluated the diagnostic accuracy of POCUS and time‐to‐interpretation for correct identification of tracheal versus esophageal intubations compared to a composite of standard‐of‐care methods in neonates. Methods: A cross‐sectional study was conducted in the Neonatal Intensive Care Unit (NICU) at Aga Khan University Hospital Karachi, Pakistan. All required intubations were performed as per NICU guidelines. The clinical team simultaneously determined the ETT placement using standard‐of‐care methods (auscultation, colorimetric capnography, and chest X‐ray) by POCUS. In addition, the clinical team was blinded to the POCUS images. Timings were recorded for each method by independent study staff. Results: A total of 348 neonates were enrolled in the study. More than half (58%) of intubations were in an emergency scenario. POCUS user interpretation showed 100% sensitivity and 94% specificity using an expert as the reference standard. We found a 99.4% agreement (Kappa: 0.96; p  < 0.001). Diagnostic accuracy of POCUS compared with at least two standard‐of‐care methods demonstrated 99.7% sensitivity, 91% specificity, and 98.9% agreement (Kappa:0.93; p  < 0.001). The median time required for POCUS interpretation was 3.0 (interquartile range [IQR] 3.0–4.0) seconds for tracheal intubation. The time recorded for auscultation and capnography was 6.0 (IQR 5.0–7.0) and 3.0 (IQR 3.0–4.0), respectively. Conclusion: POCUS is a rapid and reliable method of identifying ETT placement in neonates. Early and correct identification of airway management is critical to save lives and prevent mortality and morbidity.